Establishment of family development fund towards economic sustainability of families - Ibrahim, Kamilia; Mohd Zin, Najibah; Abdul Hak, Nora; Che Soh @ Yusoff, Roslina; Md Hashim, Noraini; Md Said, Mohd Helmi (2017)
This paper examines the issues and models related to the proposal of the setting up of a Family Fund as an alternative mode to an effective enforcement of maintenance orders. The objective being to ensure economic sustainability of families especially when divorce causes financial hardships. It is a known fact that neglected payment of maintenance due to weak enforcement procedure and lackluster family support system cause financial problems and social sufferings to the affected parties. This study which adopts data compilation from scrutiny of cases of the Malaysian Shariah courts in ten states of Malaysia based on the World Bank methodology revealed that the recurrent phenomena is primarily due to the defaulting party (men) not having the means and time, costs and procedure weaknesses in the law. The defaulting party poor financial capacity found in most cases of failure to pay maintenance endorses the need to create a family fund as a source of funding. It is noted that in Islam savings is encouraged to take care of the welfare of families. To articulate the idea of the proposed family fund the study examines various existing fund models in Malaysia and visited Morocco and Spain, which have such funds for an insight of its models. The study concludes with the proposal of setting up of the family fund, which is hoped to be a solution to the economic woes of the divorced family as well as to financially assist towards the sustainability of families with or without divorce.